Chemical characterization of silanized silver nanoparticles impregnated in poly (methyl methacrylate) resin: An in vitro study - V Thillai Nayaki; Suma Karthigeyan; Seyed Asharaf Ali; G Kalarani; Krishnaraj Ranganathan; Ajay Ranganathan (Wolters Kluwer Medknow Publications, 2023)
Aim: The intention was to determine the chemical interaction of silanized AgNPs with PMMA by Fourier transform infrared (FTIR) spectroscopy. Settings and Design: In-vitro comparative study. Materials and Methods: This study is composed of four groups - 0.75% AgNP, 1.0% AgNP, 1.5% AgNP impregnated with PMMA, and nonimpregnated PMMA as control. The chemical nature of silanized AgNPs was studied using FTIR study. Results: The results showed the appearance of new peak between 1727/cm and 1436/cm, i.e., 1636.476/ cm, 1645.886/cm, and 1646.885/cm, representing the C = C stretch in the experimental groups, i.e., 2, 3, and 4, respectively. This peak confirms that coupling agent has chemically interacted with PMMA. Conclusion: It can be concluded that the AgNPs coated with the silane coupling agent TMSPM has chemically reacted with PMMA.